Analysis of Teacher Competency with a Non-Linear Education Background in Biology Learning - Putri Handayani; Laily Alifadeyana; Fatikhatun Nikmatus Sholihah (SCHOOLAR: Social and Literature Study in Education, 2025)
This study aims to analyze the competence of teachers who have a non-linear educational background with the subject of Biology in the context of learning in schools. The research was conducted in a madrasah involving a biology teacher and 24 tenth-grade students as respondents. The method used is descriptive with qualitative and quantitative approaches through interviews and questionnaires. The results of the questionnaire showed that, in general, the competence of biology teachers with inappropriate educational backgrounds was considered quite good by students, with an average percentage of 72.9% in the good category. However, it was found that there was a tendency that students to feel more helped, motivated, and understand the material better when learning was carried out by teachers who had a background in biology education. Teachers with appropriate educational backgrounds are considered superior in terms of mastery of materials, implementation of practicums, the use of teaching aids, and learning approaches that are relevant to the characteristics of science. These findings show the importance of the suitability of teachers' educational backgrounds to the subjects taught, especially in concept-based and practice-based learning. Even if teachers with inappropriate backgrounds still show proper competence, continuous professional development efforts are needed to improve the quality of equal learning.